2022
DOI: 10.46502/issn.1856-7576/2022.16.03.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficiency of podcasts and mobile applications in the study of the german language by university students

Abstract: The article aims to study and compare the efficiency and effectiveness of podcasts and mobile applications in the study of the German language by students of the faculty of linguistics. The research involved several key stages: (1) studying scientific publications that demonstrate the experience of using the studied methods in teaching a foreign language in university; (2) selecting a sample from the 2- and the 3-year students of the faculty of linguistics, Philology; (3) the diagnostic stage that includes tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In addition, Students 3 and 4 revealed that podcasts and vodcasts improve listening skills, which helped in better understanding the module content. This finding corroborates recent studies by Oliinyk, Gaman, Chaikovska, Bezzubova, and Paustovska (2022), Yeganeh and Izadpanah (2021), Vergara (2022), and Yiemkuntitavorn and Rattanapan (2021) in that podcasts and vodcasts are accessible, assist in understanding the module content and attentive listening is essential. From a transactional distance perspective (Moore, 1993;Zhang, 2003), the accessibility of podcasts and vodcasts facilitates learning, is helpful and improves students' listening skills, thereby reducing the transactional distance between lecturers and students (see Figure 1) as the course design accommodates flexibility through communications media and students' autonomy is not compromised by the use of podcasts and vodcasts in teaching and learning.…”
Section: Paper | 831supporting
confidence: 91%
“…In addition, Students 3 and 4 revealed that podcasts and vodcasts improve listening skills, which helped in better understanding the module content. This finding corroborates recent studies by Oliinyk, Gaman, Chaikovska, Bezzubova, and Paustovska (2022), Yeganeh and Izadpanah (2021), Vergara (2022), and Yiemkuntitavorn and Rattanapan (2021) in that podcasts and vodcasts are accessible, assist in understanding the module content and attentive listening is essential. From a transactional distance perspective (Moore, 1993;Zhang, 2003), the accessibility of podcasts and vodcasts facilitates learning, is helpful and improves students' listening skills, thereby reducing the transactional distance between lecturers and students (see Figure 1) as the course design accommodates flexibility through communications media and students' autonomy is not compromised by the use of podcasts and vodcasts in teaching and learning.…”
Section: Paper | 831supporting
confidence: 91%